PENGARUH KEJELASAN SASARAN ANGGARAN, EVALUASI ANGGARAN, KOMITMEN ORGANISASI DAN DESENTRALISASI TERHADAP KINERJA APARAT PEMERINTAH DAERAH (Studi Empiris pada OPD kabupaten kepulauan Meranti 2017) - Siti Alfisa; Nasrizal Nasrizal; Eka Hariyani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2018)
This research was conducted on employees OPD kepulauan Meranti. This research was included in the quantitative research. The type of data used in this research is the primary data by source. And then, in data collections sampling was conducted with a purposive sampling method ( Sugiyono, 2014:392) with respondents as many as 69 employees who working in OPD Kepulauan Meranti. Data were analyzed using multiple regression with SPSS version 17. This research aimed to know the influence of the clarity of budget, Budget Evaluation, Organizational Commitment and Decentralization on the Performance Of Local Government Apparatus. The main problem that researcher descriptions are as follows : to see how many significant relationship between the dependent variable to the independent variable. The results of this research showed that the clarity of Budget Targets on the Performance Of Local Government Apparatus, Budget Evaluation Affect the Performance Of Local Government Apparatus, Organizational Commitment Affect the Performance of Local Government Apparatus and Decentralization to the Performance of Local Government Apparatus. Significant value 0,009, 0,000, 0,002. Contributions the influence of Clarity of Budget Targets, Budget Evaluation, Organizational Commitment and Decentralization on the Performance of Local Government Apparatus of Kepulauan Meranti amounted 79,5%. While the remaining 20,5% is influence by variables that aren’t observed in this study.Keywords : performance of Local Government Apparatus, clarity of budget, Budget Evaluation, Organizational Commitment and Decentralization